Synthesis and characterization of impurities of Apixaban drug substance—An anticoagulant. (16th May 2022) - Satheesh, Deekonda; Sreenivasulu, B.; Reddy, Bhavanam Sekhara; Reddy, U. Rajasekhar; Saladi, J. S. Chakradhar; Gupta, P. Badrinath; Reddy, Aaramadaka Sunil Kumar; Aegurla, Balakrishna; Basavaiah, Keloth
Abstract: Apixaban is an anticoagulant used to treat venous thromboembolic disorders. The present work describes the origin and synthesis of related substances of Apixaban PG ester‐1 and PG ester‐2. These impurities arise in the process of Apixaban drug substance, later these impurities are transformed into the final Apixaban drug substance. These novel synthesized impurities were characterized by 1 H NMR, 13 C NMR, HPLC, and HRMS analysis. Abstract :